Spectroscopic and Electrochemical Exploration of Carbon-Infused Intercalation-Type Spinel Composite for Aqueous Systems - Willenberg, Shane; Carleschi, Emanuela; Ross, Natasha (Frontiers in Chemistry, 2022)
Lithium-manganese-based compounds are promising intercalation host materials for aqueous battery systems due to their synergy with high ionic conductive aqueous electrolytes, safety, eco-friendliness, and low cost. Yet, due to poor electrical conductivity and trapping of diffused electrolyte cations within its crystal formation, achieving optimum cycle stability and rate capability remains a challenge. This unfortunately limits their use in modern day high-powered devices, which require quality output with high reliability. Here, the authors propose a facile method to produce LiMn2O4 and LiFe0.5Mn0.5PO4 and compare their structural stability and corresponding electrochemical performance by controlling the interfacial layer through multi-walled carbon nanotubes’ (MWCNTs) infusion. High-resolution scanning electron microscopy results revealed that the active particles were connected by MWCNT via the formation of a three-dimensional wiring network, suggesting that stronger interfacial bonding exists within the composite. As a result, the conducting composite decreases the electron transport distance with an increased number of active sites, thus accelerating the lithium ion intercalation/de-intercalation process. Compared to C/LMO with a Rct of 226.3 Ω and change transfer (io) of 2.75 × 10−3, the C/LFMPO-composite has a reduced Rct of 138 Ω and enhanced rate of 1.86 × 10−4 A cm−2. The faster kinetics can be attributed to the unique synergy between the conductive MWCNTs and the contribution of both single-phase and two-phase regions in Li1-x(Fe,Mn)PO4 during Li+ extraction and insertion. The electrochemical features before and after modification correlate well with the interplanar distance of the expanded manganese and manganese phosphate layers shown by their unique surface features, as analyzed by advanced spectroscopy techniques. The results reveal that MWCNTs facilitate faster electron transmission whilst maintaining the stability of the host framework, which makes them favorable as next generation cathode materials.